The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1074/jbc.m411759200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chloride Channel in Drosophila melanogaster Is Inhibited by Protons

Abstract: A systematic analysis of the Drosophila genome data reveals the existence of pHCl, a novel member of ligand-gated ion channel subunits. pHCl shows nearly identical similarity to glutamate-, glycine-, and histamine-gated ion channels, does however not belong to any of these ion channel types. We identified three different sites, where splicing generates multiple transcripts of the pHCl mRNA. The pHCl is expressed in Drosophila embryo, larvae, pupae, and the adult fly. In embryos, in situ hybridization detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 68 publications
2
70
0
Order By: Relevance
“…Upon raising the pH to above pH 7.3, Schnizler et al (26) observed the onset of a chloride current with a pH response (Hill number 1.07) that did not desensitize as long as the pH was in the alkaline range. Temperature (in the range of 15-30°C) is a positive modulator for the activation of these channels.…”
Section: Discussionmentioning
confidence: 99%
“…Upon raising the pH to above pH 7.3, Schnizler et al (26) observed the onset of a chloride current with a pH response (Hill number 1.07) that did not desensitize as long as the pH was in the alkaline range. Temperature (in the range of 15-30°C) is a positive modulator for the activation of these channels.…”
Section: Discussionmentioning
confidence: 99%
“…The primary target of IVM is the invertebrate glutamate-gated chloride channel (GluCl) (Cully et al, 1994(Cully et al, , 1996Janssen et al, 2007Janssen et al, , 2010McCavera et al, 2009;Moreno et al, 2010), though it also has efficacy against other members of the invertebrate Cys-loop family of neurotransmitter receptors including the γ-aminobutyric acid- (Brown et al, 2012), histamine- (Zheng et al, 2002) and pHsensitive chloride channels (Schnizler et al, 2005). Because IVM is used to control and treat parasitic nematode diseases (Õmura, 2008), the majority of research on IVM targets has occurred in nematodes or model organisms, but the function of GluCl in mosquito disease vectors is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that an inward-rectified Cl Ϫ current was induced by extracellular acidification in rat cortical astrocytes (16). Furthermore, Schnizler and colleagues (26) found that there was a novel member of ligand-gated ion channel subunits, pHCl, expressed in Drosophila; pHCl mediated a chloride current that was inhibited by extracellular protons and activated by avermectins in a pH-dependent manner, with a linear current-voltage relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Chloride channels were activated by extracellular acidification in human skeletal muscle cells (13), rat carotid body cells (21), and rat Sertoli cells (2) but were inhibited in Drosophila melanogaster (26) and Xenopus oocytes (8). Nobles and colleagues (20) showed that though some differences existed, many properties of acid-activated Cl Ϫ current are similar to those of the swelling-activated Cl Ϫ current, implying that the two currents are related and that extracellular acidification reflects a novel stimulus for volume-activated Cl Ϫ current.…”
mentioning
confidence: 99%